Comparison of Oral Stereognosis in 6 and 7 Old Normal Children - Amir Shiani; Mohammad Reza Hadian; Mohammad Akbari; Hossein Karimi; Shohreh Jalaie (University of Social Welfare and Rehabilitation Sciences, 2004)
Objective: This research determined oral stereognosis (form recognition and spent time to recognize) in normal children in north and south of Tehran city to use it in assessment and therapy of oral senses and speech in children with articulation disorders. Materials & Methods: This research was done in 200 children who were 6 & 7 years old and normal in Tehran city. 20 items with different shapes were used and children were wanted to recognize the shapes which were put in their mouth and they should choice one of three shapes located in front of them. Responses and the spent time were calculated. Results: The mean scores of form recognition in children of 6 years old is 17/34 and in children of 7 years old is 17/59. There was no significant difference between them in their scores (P=0.31). In addition, the time of formation diagnosis in 6 years old children is 2/67s (seconds) and in 7 years old children is 2/82s, there was no significant difference between them (P=0.11).The northern city children responded slower than the other group (P=0.000). The only statistically significant score between two sexes was the time of formation recognition which was shorter in girls relative to the boys (P=0.043). Conclusion: Based on this study, a significant correlation could not be found in ability of oral stereognosis in 6 and 7 years old children. But in south of city children can recognize faster than children in northern city. Based on importance of this sense in speech, we suggest normalization of it in different ages.